A Study On Metabolic Syndrome With Diabetes Mellitus (Journal of Pharmaceutical Negative Results, 2023)
BackgroundMetabolic syndrome is a cluster of abnormalities which is characterized by hyperglycaemia. This study was mainly undertaken in order to study the burden of metabolic syndrome in newly detected type 2 diabetes mellitus cases.Material and MethodsA case control study was conducted in 50 cases and 50 controls in a tertiary care centre. The cases included newly diagnosed type 2 diabetes mellitus cases. The metabolic syndrome was diagnosed by modified WHO criteria including fasting blood glucose (FBG), 2 hour post prandial blood sugar (2 hr PPBS), glycated haemoglobin (HbA1c), waist circumference (WC), hip circumference (HC), Height (H), Weight (W), high density lipoprotein cholesterol (HDL-C) and low-density lipoprotein (LDL-C), triglycerides (TG), systolic blood pressure (SBP) and diastolic blood pressure (DBP), body mass index, serum creatinine were estimated. At the baseline the blood samples were taken after minimum 6 hours overnight fasting.ResultsThe prevalence of metabolic syndrome was 22.0% in newly diagnosed diabetes cases and 14.0% of the controls. This study had shown that, 18.0% of the newly diagnosed diabetics and 98.0% of the controls were physically active. There was statistically significant difference in the fasting blood sugar levels and HbA1c. There was no statistically significant difference in the triglyceride level, total cholesterol, HDL, LDL and VLDL levels. A statistically significant difference was observed in the microalbumin levels between the cases and controls.ConclusionThis study concluded that, the metabolic syndrome was significantly higher in newly detected diabetes mellitus patients when compared to controls.